Etnobotani dan Etnoekologi: Sebuah Perbandingan - Ahmad Sholehuddin Suryanullah; Ahmad Asron Mundofi (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2024)
Ethnobotany was proposed by North American botanist John Harshberger in 1895, its emergence aimed to understand the relationship between humans and plants in the environment where they live. While ethnoecology was first introduced by the German philosopher Friedrich Ratzel in 1866, the emergence of this study aims to understand the interactions between humans and their environment. This article attempts to explain developments, review the comparison between ethnobotany and ethnoecology, and see their relevance in Indonesia. The literature study method was used in the process of compiling the narrative in this article. The results of this research show that ethnobotany and ethnoecology have similarities in data collection methods, use of the language spoken by the research subjects, and both study nature. While the difference is that ethnobotany focuses more on the study of plants and ethnoecology focuses on studying the environment, the next difference concerns the nature of objects, ethnobotany discusses living objects, while ethnoecology can discuss living and inanimate objects. Apart from that, ethnobotany and ethnoecology are very relevant when applied in Indonesia, because they can provide new alternatives for cultural studies in Indonesia.